ChemInform Abstract: High‐Concentration Na Doping of SrRuO3 and CaRuO3. Issue 27 (8th July 2014) - Seki, Hayato; Yamada, Ryuta; Saito, Takashi; Kennedy, Brendan J.; Shimakawa, Yuichi
Abstract Highly Na‐doped perovskite‐type ruthenates Sr1‐xNaxRuO3 (x = 0, 0.12, 0.25, 0.50, 0.75) and Ca1‐yNayRuO3 (y = 0, 0.10, 0.20, 0.50) are prepared by solid state reaction of stoichiometric amounts of SrCO3 or CaCO3 and Ru metal (1273 K, 12 h in air), followed by high temperature/high pressure treatment of the obtained powders in the presence of Na2O2 (Au capsules, 6—9 GPa, 1173 K, 30 min).